Enfants gitans à l'école et en famille D'une analyse des dynamiques langagières en famille aux pratiques de classe - Auger, Nathalie (Éducation et savoirs en société, 2021)
This book aims to answer a controversial question in our society: how to help the children of gypsy communities to succeed in school? For a long time, the gypsy community has been singled out as being on the margins, difficult to educate because often absent, living in a multilingual environment (a home language different from school) and particularly impoverished. The challenge of working on and with these children who are also students, beyond the possible benefits for their academic success, is to highlight the linguistic and teaching approaches that would allow the school to include all children, whatever their real or imaged specificities might be, in order to teach all groups more effectively, including those who do not have any academic "problem" to start with. This book, intended for researchers and students of language sciences, didactics, education and related disciplines (sociology, anthropology, etc.), is also accessible to teachers regardless of their teaching subject, as well as to families and the general public. From the strict point of view of research, the original nature of the project is to rely on (socio)linguistics, development and didactics - fields rooted in language sciences. Our objective is to approach the phenomenon of academic difficulty through the medium of languages (in the family and at school) and their acquisition, while including the social dimensions and didactic implications of this reflection.